Genetic and Biochemical Analysis of PadR-padC Promoter Interactions during the Phenolic Acid Stress Response in Bacillus subtilis 168 - Nguyen, Thi Kim Chi (American Society for Microbiology, 2011)
Bacillus subtilis 168 is resistant to phenolic acids by expression of an inducible enzyme, the phenolic acid decarboxylase (PadC), that decarboxylates these acids into less toxic vinyl derivatives. In the phenolic acid stress response (PASR), the repressor of padC, PadR, is inactivated by these acids. Inactivation of PadR is followed by a strong expression of padC. To elucidate the functional interaction between PadR and the padC promoter, we performed (i) footprinting assays to identify the region protected by PadR, (ii) electrophoretic mobility shift assays (EMSAs) with a modified padC promoter protected region to determine the interacting sequences, and (iii) random mutagenesis of padR to identify amino acid residues essential for the function of PadR. We identified an important consensus dyad sequence called IR1-2 (ATGT-8N-ACAT) overlapping a second dyad element (GTGT-8N-ACAT) that we named dIR1-2bis. The entire dIR1-2bis/IR1-2 sequence permits binding of two PadR dimers in EMSAs, which may be observed for bacteria grown under noninduced conditions where the padC promoter is completely repressed. Three groups of modified PadRs giving a PASR phenotype were characterized in vivo. The DNA sequences of certain mutant padR alleles indicate that important residues are all located in the region containing the coiled-coil leucine zipper domain that is involved in dimerization. These substitutions reduce the affinity of PadR binding to the padC promoter. Of particular interest are residue L128, located at the center of the putative coiled-coil leucine zipper domain, and residue E97, which is conserved among all PadRs.